The Influence of Marketing Mix and Cafe Atmosphere on Customer Loyalty Through Customer Satisfaction As a Mediation Variable - M. Risal; Achmad Efendi; Adi Firmanzah (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The development of cafes and restaurants represents one of the fastest-growing sectors in Indonesia's culinary industry. This growth is evident not only in major cities but also in remote areas. As lifestyles become more sophisticated, the increasing needs of the community are driving changes in consumption patterns.Purpose: This study aims to examine the role of the marketing mix and café atmosphere on customer loyalty, mediated by customer satisfaction, in cafes and restaurants in Samarinda City.Design/Methodology/Approach: A total of 100 café and restaurant owners participated in this study. Data were analyzed using SmartPLS 3.3.Findings/Results: The results show that the marketing mix significantly influences customer satisfaction through factors such as fair pricing, appealing products, effective promotions, and strategic locations, which meet consumer expectations. Similarly, the café atmosphere, characterized by pleasant lighting, comfortable seating, and enjoyable background music, enhances customer satisfaction. Both the marketing mix and café atmosphere contribute to customer loyalty, as consumers are willing to return and recommend these establishments when they feel satisfied. Additionally, customer satisfaction itself plays a crucial role in fostering loyalty, demonstrating that a positive experience with pricing, products, promotions, and ambiance leads to higher retention rates.Conclusion: The marketing mix, café atmosphere, and customer satisfaction significantly influence customer loyalty. Each variable and its indicators play a critical role in shaping consumer behavior.Originality/Value (State of the Art): While the marketing mix and café atmosphere have been studied conceptually and theoretically, research on café atmosphere remains limited. This study contributes to the field by exploring a specific research object, including a distinct sample size, providing valuable insights for further research in this area. Keywords: café atmosphere, customer satisfaction, customer loyalty, marketing mix, café and restaurant